2006
DOI: 10.1177/0361198106198800115
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Small Roundabouts with Two-Lane Entries

Abstract: Roundabouts have been a popular system for intersections outside downtown zones in urban areas in Switzerland for more than 10 years. One form of small roundabout becoming more common in Switzerland is the system with short two-lane approaches and a single-lane extrawide circulatory roadway. Research shows that small roundabouts with two-lane entries with a single-lane extrawide circulatory roadway have capacities 20% to 30% higher than those with single-lane entries, although the space requirements are almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…Several studies demonstrated speed reductions at single-lane roundabouts. However, when roundabouts with multiple lanes offer higher capacities [18], their speed and behavior control is less efficient [19]. Increasing the number of lanes allows drivers greater freedom in their behavior, leading to an increase in potential conflicts [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated speed reductions at single-lane roundabouts. However, when roundabouts with multiple lanes offer higher capacities [18], their speed and behavior control is less efficient [19]. Increasing the number of lanes allows drivers greater freedom in their behavior, leading to an increase in potential conflicts [20].…”
Section: Introductionmentioning
confidence: 99%
“…O valor médio do gap crıtico encontrado no estudo de Hagring et al (2003) foi de 4,08 segundos para a faixa da direita e 4,36 segundos para a faixa da esquerda, enquanto o follow-up headway médio foi de 2,64 segundos. Lindenmann (2006), em seu estudo aplicado na Suıḉa, a irma que os veıćulos da faixa da esquerda, por ter condições de visibilidade melhor, tendem a partir antes para entrar na rotatória. Em contrapartida, os veıćulos da faixa da direita trafegam com um follow-up headway menor.…”
Section: Contextualização Teóricaunclassified
“…Em contrapartida, os veıćulos da faixa da direita trafegam com um follow-up headway menor. Lindenmann (2006) encontrou o valor de 3,49 segundos de gap crıtico para a faixa da esquerda e 3,45 segundos para a faixa da direita e, ao analisar as duas faixas em conjunto, encontrou uma média de 3,65 segundos. O follow-up headway encontrado nos estudos da Suıḉa foi 2,73 segundos para a faixa da esquerda e 2,55 segundos para a faixa da direita.…”
Section: Contextualização Teóricaunclassified